Radiographic Evaluation of Bone Adaptation Adjacent to Percutaneous Osseointegrated Prostheses in a Sheep Model - Jeyapalina, Sujee (Springer US, 2014)
BACKGROUND: Percutaneous osseointegrated prostheses (POPs) are being investigated as an alternative to conventional socket suspension and require a radiographic followup in translational studies to confirm that design objectives are being met. QUESTIONS/PURPOSES: In this 12-month animal study, we determined (1) radiographic signs of osseointegration and (2) radiographic signs of periprosthetic bone hypertrophy and resorption (adaptation) and (3) confirmed them with the histologic evidence of host bone osseointegration and adaptation around a novel, distally porous-coated titanium POP with a collar. METHODS: A POP device was designed to fit the right metacarpal bone of sheep. Amputation and implantation surgeries (n = 14) were performed, and plane-film radiographs were collected quarterly for 12 months. Radiographs were assessed for osseointegration (fixation) and bone adaptation (resorption and hypertrophy). The cortical wall and medullary canal widths were used to compute the cortical index and expressed as a percentage. Based on the cortical index changes and histologic evaluations, bone adaptation was quantified. RESULTS: Radiographic data showed signs of osseointegration including those with incomplete seating against the collar attachment. Cortical index data indicated distal cortical wall thinning if the collar was not seated distally. When implants were bound proximally, bone resorbed distally and the diaphyseal cortex hypertrophied. CONCLUSIONS: Histopathologic evidence and cortical index measurements confirmed the radiographic indications of adaptation and osseointegration. Distal bone loading, through collar attachment and porous coating, limited the distal bone resorption. CLINICAL RELEVANCE: Serial radiographic studies, in either animal models or preclinical trials for new POP devices, will help to determine which designs are likely to be safe over time and avoid implant failures.